LGG-21. LONG-TERM OUTCOME OF PATIENTS WITH PEDIATRIC TECTAL GLIOMA. Issue 2 (22nd June 2018) - Liu, Anthony; Harreld, Julie; Jacola, Lisa; Gero, Madelyn; Acharya, Sahaja; Chiang, Jason; Ghazwani, Yahya; Wu, Shengjie; Klimo, Paul; Gajjar, Amar; Qaddoumi, Ibrahim
Abstract: Tectal glioma (TG) is an uncommon pediatric low-grade tumor with limited data on long-term outcome. A retrospective review of TG diagnosed in patients ≤ 21 years at our center between 1986 and 2013 identified 19 patients (males=13; median age at diagnosis=10 years [yrs]; range, 0.01-19.99). All patients were diagnosed based on MRI. Initial CSF diversion was necessary in 16 patients (ventriculoperitoneal [VP] shunt= 10; endoscopic third ventriculostomy=6). Ommaya reservoir was inserted in 5 patients. VP shunt revisions (1-12 times) were required in 7 patients; while 2 patients had subdural hematoma due to over-shunting. Biopsy or resection was performed in 7 patients (upfront=5, at progression=2), with histology showing pilocytic astrocytoma (n=6) or low-grade glioma, NOS (n=1). Duplication of chromosome 7q34, marker of KIAA1549-BRAF fusion, was detected in 2 of 4 patients tested. Adjuvant therapy was delivered in 8 patients mostly upon progression, and included focal radiation (n=4), systemic therapy (n=3), or a combination (n=1). The median duration of follow-up was 9.57 yrs (range, 3.64-16.98): 7 experienced progression at median of 0.68 yrs (range, 0.28-8.98), including 2 with metastases. One patient each died due to suicide, obstructive hydrocephalus, and suspected shunt malfunction. Respective 5- and 10yr overall-survival were 92.9 ± 6.9% and 85.1 ± 9.7%. Long-term morbidities included persistent headache (n=8) and visual symptoms (n=7). Significant impairments were seen on measures of intelligence (n=2/9; 22%), working memory (n=2/7; 29%), and processing speed (n=6/6; 100%). Long-term survival of children with TG is satisfactory. Regular follow-up is recommended due to risks of shunt failure, progression, and long-term morbidities.